Relationships between university students’ temporal perceptions of affective and cognitive attributes of academic performance - Castañeda Figueiras, Sandra (2023)
Introduction: The variations of the intentional monitoring carried out by university students on attributes and temporalities of complex learning are analyzed. Objective: to identify the structural relationships between affective and cognitive attributes considered at different times of performance in two tasks of academic skills. Method: intentional sample of 420 students of Higher Education of Mexico and Colombia, of both sexes, answered: a) an inventory of the self-report on variations in attributes and temporal moments in two different tasks and b) two tests, one of comprehension of texts and another of mathematical skills. The theoretical models underlying the assumed academic performance were validated, empirically, through path analysis. Results: high rates of practical fit in all models, which allows identifying differential influences depending on the temporal condition in which the attributes operate, retrospective in the affective and concurrent in the cognitive. Discussion: the findings configure theoretical advances on the impact of temporality on the dispositions that students must show to act intentionally (that is, to be endowed with agency), in order to generate the transformations that their goals demand. These can serve as efficient markers for diagnostic artifacts, as well as for didactic procedures in the service of expert development.